TRANSLATION STRATEGY IN TOBA DREAM MOVIE SUBTITLE - Elisa Betty Manullang; Gabe Hartina Marpaung (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
The article deals with the translation strategies used in Toba Dream Movie. The objectives of this study were to find out types and most dominant type of translation strategies used in the subtitles of Toba Dream movie. The study was conducting by using descriptive qualitative method. The data of the study were words, phrases, and clauses in the subtitle of Toba Dream movie, there were 425 dialogues in the movie. The data analysis were taken by listing and tabulating the data. The data were analyzed based on the theory that proposed by Henrik Gottlieb. The findings inducted that there were ten types of translation strategies used in the movie, they were there were (319 times)used transfer strategy, (37 times) used paraphrase, (27 times) used dislocation, (20 times)used resignation, (10times) used expansion, (5 times)used decimation, (4 times) utterances which used condesation, (1time) used imitation, (1time) used transcription and (1time) used deletion. The dominant strategy used in the subtitles of Toba Dream movie was transfer strategy where the translator translated the dialogues completely and correctly.